Beauveria bassiana with flupyradifurone for the control of Trialeurodes vaporariorum Vuill in French beans crop - Toledo-Perdomo, Claudia Elizabeth (2019)
Introduction. Trialeurodes vaporariorum (Westwood) is one of the main pests of the French bean (Phaseolus vulgaris L.), legume for consumption in inmature pods, and is a vector of the golden mosaic virus, which affects the quality and yield of the crop reaching losses of up to 100%, being difficult to control because many chemicals no longer control the pest. The French bean within the non-traditional products in Guatemala, occupies the second place in the export. Ensuring a good phytosanitary management with low chemical load by pesticides are important factors to be able to export it. Objective. The objective of the investigation was to determine the effectiveness of the combination between Flupyradifurone and Beauveria bassiana for the control of whitefly in French bean cultivation. Materials and methods. The study was conducted from February to December 2018 in Parramos, Chimaltenango, Guatemala. Seven plots of 100 m² were established corresponding to each treatment. Weekly, whiteflies were sampled during two cultivation cycles, and natural enemies of these were also collected on each plot. Three applications of each treatment were made in each crop cycle, and the plants were sampled divided into three strata (high, medium, low). Results. The treatments that showed the best control of the whitefly population (nymphs and adults) when performing the Tukey test (0,05), were flupyradifurone (1 l ha-1) + B. bassiana, and flupyradifurone (0.75 l ha-1) + B. bassiana. The largest distribution of whitefly populations was found in the upper and middle strata. Conclusion. The combination of flupyradifurone (0,05) with B. bassiana can be used within an integrated pest management, and is presented as an alternative control of whiteflies, which has acquired resistance to some agrochemicals.